KOMPOSISI PROKSIMAT IKAN SEPAT RAWA (Trichogaster trichopterus Pall) CRISPY MENGGUNAKAN PERISA INSTANT - Hafni Rahmawati; Siti Aisyah (Fish Scientiae, 2018)
Three-spot gourami is the most important fish commodity in East Borneo. The fish was only processed into fried salted fish and fermented fish such as wadi and bekasam until right now. The research of three-spot gouramy was only limited to fish salting and drying. One of the fish diversification processed was frying presto product that called fish crispy that has crisp and crunchy chacarteristics so its comfort to consume, adding with instant flavor (cheese, barbeque and sweet spicy) to increase product taste. There search on the fish crispy panelists acceptance with the addition of instant flavor produced the highest color and texture in cheese flavoring while the highest aroma and flavor value was in barbeque flavoring. The proximate composition of the product hasnot been analyzed. This study aims to learn the proximate composition and calcium of fish crispy using different instant flavoring. The treatment consisted of O (without seasoning), A (15% instant cheese flavoring), B (15% instant barbeque flavoring) and C(15% sweet spicy flavoring). Based on the proximate test, the treatment has a different effect on water, protein, fat and ash content. The B (barbeque) treatment is the best where the highest protein value is 58.24%.